The late Oligocene flora from the Río Leona Formation, Argentinian Patagonia - Cesari, Silvia Nelida; Panti, Carolina; Pujana, Roberto Roman; Francis, Jane E.; Marenssi, Sergio Alfredo (Review of Palaeobotany and Palynology)
A late Oligocene plant macrofossil assemblage is described from the Río Leona Formation, Argentinian Patagonia. This includes a fern, “Blechnum” turbioense Frenguelli, one species of conifer, and sixteen angiosperm taxa. Rosaceae, Myrtaceae, Proteaceae, Lauraceae, Anacardiaceae and Typhaceae are represented by one species in each family. Five species are considered to be members of the Fabales. Three leaf taxa together with Carpolithus seeds are placed in the Nothofagaceae. Palynomorphs and permineralized woods complete the floral record of the Río Leona Formation, which is considered early late Oligocene based on radiometric dating and palynofloras. Fil: Cesari, Silvia Nelida. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Panti, Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Francis, Jane E. British Antarctic Survey High Cross; Reino Unido Fil: Marenssi, Sergio Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Basicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Basicas, Aplicadas y Ambientales de Buenos Aires; Argentina